(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: Summarize the treatment outcomes of Montelukast in patients with allergic rhinitis and concomitant asthma. Methods: A narrative review of studies on Montelukast treatment in patients with allergic rhinitis and concomitant asthma published between January 2000 and December 2025. Results: A total of 16 studies involving 11,174 patients were included in the analysis. Study designs included randomized controlled trials and cohort observational studies. In studies evaluating allergic rhinitis symptoms, 11 of 13 studies reported post-treatment improvement, with 8 studies demonstrating statistically significant results. Asthma-related outcomes, including asthma symptoms, pulmonary function, and rescue medication use, also showed improvement trends, with 9 of 10 studies reporting improvement in asthma symptoms and 8 of 11 studies showing improvement in pulmonary function. Quality of life improved in all 4 studies assessing this outcome. Among the 11 studies evaluating safety, Montelukast was generally well tolerated, and most adverse events were mild in severity. Conclusion: Montelukast demonstrated a role in improving allergic rhinitis and asthma symptoms in patients with both conditions, particularly when used as part of combination treatment strategies.